2004
DOI: 10.2175/106143004x141889
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxygen Demand Reduction Of Various Wastewater Types Using Magnetic Field‐assisted Fenton Reaction

Abstract: Constant magnetic field (CMF) was investigated for its potential to intensify chemical oxygen demand (COD) removal in wastewater when applied with a generalized Fenton reaction. Various types of industrial and domestic wastewater were tested in the experiment. A significant dependence was observed between the wastewater type, dose of reacting substances, time of exposure to CMF, effectiveness of COD removal, and the rate of the advanced oxidation process. The use of CMF resulted in the improvement of the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A MF is a force field analogous to gravitational and electrical fields; in other words, surrounding a source of potential, there is a contoured sphere of effect or field (Krzemieniewski et al, 2004;Xu et al, 2010). In the case of gravitation, the source of potential is a mass.…”
Section: Mfsmentioning
confidence: 99%
“…A MF is a force field analogous to gravitational and electrical fields; in other words, surrounding a source of potential, there is a contoured sphere of effect or field (Krzemieniewski et al, 2004;Xu et al, 2010). In the case of gravitation, the source of potential is a mass.…”
Section: Mfsmentioning
confidence: 99%
“…Dilution of 50 times or more with drinking water has been a common practice before discharging these wastewaters into the sewage system, which is not a sustainable strategy for the 21st century. The treatment of wastewaters from the timber industry using chemical methods has shown limited efficiency [3]. The use of biological treatment [1] and sorption/filtration processes [2] has also shown limitations when the main purpose is to comply with established standards for discharges into recipient water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…MF can also influence the lifetime of radicals by inhibiting their recombination reactions through the interaction with electron spins [21]. Krzemieniewski et al found that MF enhances the Fenton process [22,23]. Hao et al reported as well that MF accelerates the decomposition rate of H 2 O 2 and the conversion rate of Fe 2+ in Fenton reaction [24].…”
Section: Introductionmentioning
confidence: 99%